2020
DOI: 10.1016/j.ijid.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of combinations of eight antimicrobial agents against Mycobacteroides abscessus complex

Abstract: A standard treatment regimen against Mycobacteroides abscessus complex (MABC) infections has not yet been established, making MABC difficult to treat successfully. In this study, we sought to develop an active ingredient for the clinical treatment of MABC infections. Methods: We screened 102 MABC strains isolated from clinical specimens using DNA sequence analysis with the housekeeping genes hsp65 and rpoB. Drug susceptibility testing was performed against two subspecies-Mycobacteroides abscessus subsp. absces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Although only a quarter of isolates (22 isolates, 25.6%) were susceptible to IPM, synergistic effects of IPM with CLR and LZD were reported ( 15 , 16 ), and a systematic review showed that IPM was associated with a higher success rate ( 3 ). Therefore, IPM might be justifiable for MABS pulmonary disease treatment despite the relatively low susceptibility rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a quarter of isolates (22 isolates, 25.6%) were susceptible to IPM, synergistic effects of IPM with CLR and LZD were reported ( 15 , 16 ), and a systematic review showed that IPM was associated with a higher success rate ( 3 ). Therefore, IPM might be justifiable for MABS pulmonary disease treatment despite the relatively low susceptibility rate.…”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin is a crucial agent for the treatment of complex Mabs infections (Shirata et al, 2020). However, the primary reason for treatment failure is inducible resistance (Nash et al, 2009;Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%